Sexual Rehabilitation of Cancer Patients: A Less Noticed Domain in Cancer Care - Abhijeet Dhawalram Faye (http://dharmais.co.id/, 2023)
Background: Sexual problems are associated with almost all types of cancers, especially those of the genital regions. Sexual problems can occur due to cancer itself or due to its treatment (chemotherapy, radiotherapy, or surgery) across all the stages of cancer and its management.Methods: The researcher reviewed the current research status of this less-discussed issue. 115 articles were identified using predefined keywords in Pubmed, Pubmed Central, Embase, and Google Scholar databases from January 1, 2000, to March 31, 2022. First, the articles were screened based on the abstracts followed by checking for the availability of their full-text versions. A total of 28 articles fulfilling the inclusion criteria were finally selected and analyzed. Results: Common sexual problems found in men were erectile dysfunction, decreased libido, dry ejaculation, and performance anxiety. On the other hand, women usually complained of reduced intimacy, lack of sexual desire, vaginal dryness, pain during intercourse, lack of sexual sensation, and reduced self-esteem for sexual activities. There is a significant prevalence of sexual problems with effects on marital relationships in cancer patients. Psychiatric disorders were found to be associated with a higher prevalence of sexual dysfunction ranging from 70 to 90% compared to the general population. Up to 50% and 40% of female and male patients with depression (a common occurrence in cancer) respectively may have sexual dysfunctions. Conclusions: Management of these problems is necessary, as it can be a contributing factor to the poor quality of life. Communication and discussion about sexual health from patients as well as the healthcare provider side are needed. The urgency of seeking a specialist’s help such as a psychiatrist or a sex therapist is also discussed. The researcher reviewed common sexual problems, causes, and treatment modalities, and suggested a few recommendations for making sexual health a part of routine cancer check-ups.